Olahraga tradisional pemuda lompat batu di korong tanjung basung II kecamatan batang anai kabupaten padang pariaman - Yustinus Gulo; herman zoni (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2019)
The problem in this study is the lack of interest of the people of Nias, especially young people in the torong basung II towards the Traditional Jumping Rock. For this reason, the researcher intends to conduct research to find out more about the Traditional Rock Jumping Sports in Korong Tanjung Basung II. This type of research is qualitative, data collection techniques carried out through observation, interviews, and documentation studies. The data obtained will be presented according to the results found. Through informants namely Penghulu, Datuk, Trainer, and Youth Korong Tanjung Basung II. The results of this study about the traditional sport of stone jumping in Korong Tanjung Basung II Pariaman: the origin of the traditional stone jumping sport in korong tanjung basung II was established in 2011. The values ​​contained in traditional stone jumping sports include moral values, courage, personality and physical . Factors that influence include economic factors, the influence of other sports and the influence of technology that is developing so as to make traditional sports lag behind. Nias youth's interest in traditional stone jumping.